Optimasi Jaringan dengan Spanning Tree untuk Congestion Management - Mayliana Mayliana (Bina Nusantara University, 2014)
A proper network optimization is needed to deal with problems on the network and to minimize latency in the data flow in a dense network. The data stream is directed into the right channels so that the optimal network speed and latency can be minimized. Spanning tree is one of the algorithms that can be used. The purpose of the Spanning tree is to prevent and reduce the loops in the network by negotiating free path and as well as to increase network uptime through redundancy (back-up). To comprehend spanning tree, the first important thing to know is how bridges and switches perform their functions. The more switches used, the use of the spanning tree becomes more important. With the spanning tree protocol, a broadcast storm can be prevented that can achieved network optimization.